Potential antioxidant effect of fruit peels for human use from northern peru, compared by 5 different methods [Potencial efecto antioxidante de las cáscaras de frutas para uso humano del norte de perú, comparado por 5 métodos diferentes] - Ganoza-Yupanqui M.L. (2021)
This research was funded by Fondo Nacional de Desarrollo Cient?fico, Tecnol?gico y de Innovaci?n Tecnol?gica (FONDECYT) del Consejo Nacional de Ciencia Tecnolog?a e Innovaci?n Tecnol?gica (CONCYTEC) del Gobierno de Per? (Convenio de Subvenci?n 153-2015-FONDECYT). The authors would like to thank Dr. Pedro Alva-Plasencia, principal researcher of the project PIC 06-2014, for providing the laboratory equipment.